Through the doors of perception to function in arbuscular mycorrhizal symbioses. Issue 4 (28th May 2014) - Bucher, Marcel; Hause, Bettina; Krajinski, Franziska; Küster, Helge
Summary: The formation of an arbuscular mycorrhizal (AM) symbiosis is initiated by the bidirectional exchange of diffusible molecules. While strigolactone hormones, secreted from plant roots, stimulate hyphal branching and fungal metabolism, fungal short‐chain chitin oligomers as well as sulfated and nonsulfated lipochitooligosaccharides (s/nsMyc‐LCOs) elicit pre‐symbiosis responses in the host. Fungal LCO signals are structurally related to rhizobial Nod‐factor LCOs. Genome‐wide expression studies demonstrated that defined sets of genes were induced by Nod‐, sMyc‐ and nsMyc‐LCOs, indicating LCO‐specific perception in the pre‐symbiosis phase. During hyphopodium formation and the subsequent root colonization, cross‐talk between plant roots and AM fungi also involves phytohormones. Notably, gibberellins control arbuscule formation via DELLA proteins, which themselves serve as positive regulators of arbuscule formation. The establishment of arbuscules is accompanied by a substantial transcriptional and post‐transcriptional reprogramming of host roots, ultimately defining the unique protein composition of arbuscule‐containing cells. Based on cellular expression profiles, key checkpoints of AM development as well as candidate genes encoding transcriptional regulators and regulatory microRNAs were identified. Detailed functional analyses of promoters specified short motifs sufficient for cell‐autonomous gene regulation in cells harboring arbuscules, and suggested simultaneous, multi‐level regulation of the mycorrhizal phosphate uptake pathway by integrating AM symbiosis and phosphate starvation response signaling.